2015 Annual Report of the American Association of Poison Control Centers' National Poison Data System (NPDS): 33rd Annual Report. (25th November 2016) - Mowry, James B.; Spyker, Daniel A.; Brooks, Daniel E.; Zimmerman, Ashlea; Schauben, Jay L.
Abstract: Introduction: This is the 33rd Annual Report of the American Association of Poison Control Centers' (AAPCC) National Poison Data System (NPDS). As of 1 January 2015, 55 of the nation's poison centers (PCs) uploaded case data automatically to NPDS. The upload interval was 9.52 [7.40, 13.6] (median [25%, 75%]) minutes, creating a near real-time national exposure and information database and surveillance system. Methods: We analyzed the case data tabulating specific indices from NPDS. The methodology was similar to that of previous years. Where changes were introduced, the differences are identified. Poison center cases with medical outcomes of death were evaluated by a team of medical and clinical toxicologist reviewers using an ordinal scale of 1-6 to assess the Relative Contribution to Fatality (RCF) of the exposure. Results: In 2015, 2, 792, 130 closed encounters were logged by NPDS: 2, 168, 371 human exposures, 55, 516 animal exposures, 560, 467 information calls, 7657 human confirmed nonexposures, and 119 animal confirmed nonexposures. US PCs also made 2, 695, 699 follow-up calls in 2015. Total encounters showed a 3.42% decline from 2014, while health care facility (HCF) human exposure cases increased by 5.09% from 2014. All information calls decreased by 15.5% but HCF information calls increased 2.67%, and while medication identification requests (Drug ID) decreased 31.7%, human exposures reported to US PCs were essentially flat, increasing by 0.149%. Human exposures with less serious outcomes have decreased 2.95% per year since 2008 while those with more serious outcomes (moderate, major or death) have increased by 4.34% per year since 2000. The top 5 substance classes most frequently involved in all human exposures were analgesics (11.1%), household cleaning substances (7.54%), cosmetics/personal care products (7.41%), sedatives/hypnotics/antipsychotics (5.83%), and antidepressants (4.58%). Sedative/Hypnotics/Antipsychotics exposures as a class increased the most rapidly (2597 calls (11.4%)/year) over the last 14 years for cases showing more serious outcomes. The top 5 most common exposures in children age 5 years or less were cosmetics/personal care products (13.6%), household cleaning substances (11.2%), analgesics (9.12%), foreign bodies/toys/miscellaneous (6.45%), and topical preparations (5.33%). Drug identification requests comprised 35.0% of all information calls. NPDS documented 1831 human exposures resulting in death with 1371 human fatalities judged related (RCF of 1-Undoubtedly responsible, 2-Probably responsible, or 3-Contributory). Conclusions: These data support the continued value of PC expertise and need for specialized medical toxicology information to manage more serious exposures, despite a decrease in calls involving less serious exposures. Unintentional and intentional exposures continue to be a significant cause of morbidity and mortality in the US. The near real-time, always current status of NPDS represents a national public health resource to collect and monitor US exposure cases and information calls. The continuing mission of NPDS is to provide a nationwide infrastructure for surveillance for all types of exposures (e.g., foreign body, viral, bacterial, venomous, chemical agent, or commercial product), the identification of events of public health significance, resilience, response and situational awareness tracking. NPDS is a model system for the real-time surveillance of national and global public health.